NIU visit - Hafizoah, Kassim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
2 July 2012. The CMLHS – NIU collaboration on the Bahasa Melayu for International Students (BmfIS) program is on its second successive year. To strengthen the collaboration, two representatives from NIU visited CMLHS on 2 July 2012. Deborah Pierce, Associate Provost, the Division of International Programs and Christopher McCord, Dean, Smerge Endowed Dean’s Chair, College of Liberal Arts & Science came on a one-day academic visit.